2008
DOI: 10.1542/peds.2008-0556
|View full text |Cite
|
Sign up to set email alerts
|

Food Security, Maternal Stressors, and Overweight Among Low-Income US Children: Results From the National Health and Nutrition Examination Survey (1999–2002)

Abstract: Younger children in food secure, low-income households in the United States who are experiencing higher levels of maternal stressors have a greater probability of being overweight than food insecure children. This finding was contrary to the hypothesis; 3 reasons for this are covered in the article. Those who create policies that address childhood obesity could consider the benefits to low-income children's well-being resulting from reducing their mothers' stressors. Because most children in the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
155
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 88 publications
7
155
3
Order By: Relevance
“…58 Other parental stressors that influence BMI levels in children include violence, serious life events, food or housing insecurity, maternal depression or substance abuse, and paternal incarceration. [59][60][61][62][63][64][65][66][67] For many studies, SES was a controlled variable in order to determine associations with other psychosocial stressors, but an article by Garasky et al 68 found that financial strain was positively associated with children being overweight or obese.…”
Section: Sleepmentioning
confidence: 99%
“…58 Other parental stressors that influence BMI levels in children include violence, serious life events, food or housing insecurity, maternal depression or substance abuse, and paternal incarceration. [59][60][61][62][63][64][65][66][67] For many studies, SES was a controlled variable in order to determine associations with other psychosocial stressors, but an article by Garasky et al 68 found that financial strain was positively associated with children being overweight or obese.…”
Section: Sleepmentioning
confidence: 99%
“…Variables tested for inclusion in the risk index were maternal BMI, [20][21][22] gestational weight gain, 20,[23][24][25] maternal education, 26,27 smoking, 20,[28][29][30] social support, 31 food insecurity during pregnancy, [32][33][34] and stress at 1 year postpartum. 34 Maternal BMI was calculated from measurements taken at the initial prenatal visit during the first trimester and categorized as normal or underweight (,25), overweight (25-,30), or obese ($30). 35 A detailed description of gestational weight gain methods is given elsewhere.…”
Section: Obesity Risk Indexmentioning
confidence: 99%
“…4,5 In children, many studies have demonstrated increased risk of obesity, [6][7][8][9][10][11][12][13] although the results have been mixed. 4,5,[14][15][16][17][18][19] Less research has explored potential pathways through which household food insecurity is related to child weight, especially in families with young infants. Given that Hispanic infants are more likely to be overweight than infants of other ethnicities 20 and to live in foodinsecure households, 2 it is particularly important to understand these potential pathways in this high-risk group.…”
mentioning
confidence: 99%